Dissection of the Interplay between Class I PI3Ks and Rac Signaling in Phagocytic Functions - Carlotta Costa; Giulia Germena; Emilio Hirsch (The Scientific World Journal)
Phagocytes, like neutrophils and macrophages, are specialized cells evolved to clear infectious pathogens. This function resides at the core of innate immunity and requires a series of concerted events that lead first to migration to the infected tissue and then to the killing of the invading pathogens. Molecular mechanisms underlying these processes are starting to emerge and point to the interplay between two families of crucial proteins: the PI3K lipid kinases and the Rac GTPases. This review focuses on how these two protein families contribute to migration, phagocytosis, and reactive oxygen species production, as well as their epistatic and feedback relations that finely tune these crucial aspects of the immune response.